Ensemble Measurement Model of E-Learning Implementation Readiness for Higher Education Institution - Artwodini Muqtadiroh, Feby; Ma'ady, Mochamad Nizar Palefi; Rizal Rahman, Faisal (IJAIT (International Journal of Applied Information Technology), 2018)
The low level of student readiness in implementing e-learning can achieve not optimal benefits or even generate losses. In fact, its failures are able to impact on swelling of the institutional funds. Therefore, it is so important to measure the level of student readiness for avoiding the impact of e-learning implementation failures. In this study, we employed an ensemble model for measuring e-learning readiness level by using the model of Akaslan & Law and Aydin & Tasci. The data were obtained from questionnaires based on the factor of technology, people, content, institutions, acceptance for e-learning, and training for e-learning. With a questionnaire consisting of questions and five Likert scales, the survey was conducted in several departments who have implemented e-learning. We assessed the results by Akaslan & Law to measure the level of student readiness and Aydin & Law for determining its readiness By assessing the level of difficulty of e-learning implementation, we show a different way of assessment that the model of Akaslan & Law can also be used for the same variables related to Aydin & Tasci model in the measurement. We work in hand together between the model of Akaslan & Law and Aydin & Tasci for the sake of knowing the level of e-learning implementation readiness in such a different way. We observed e-learning of Institut Teknologi Sepuluh Nopember (ITS) or so-called ShareITS and found that ITS students are ready to implement e-learning.